Treatments of Advanced Non‑Small Cell Lung Cancer (NSCLC) in an Italian Center: Drug Utilization and the Treatment Costs of Innovative Drugs - Piantedosi, Francovito; Cerisoli, Raffaela; Battiloro, Ciro; Andreozzi, Francesca; Vitiello, Fabiana; Gilli, Marina; De Marino, Valeria; Letizia, Antonietta; Bianco, Antonella; Caprice, Ivana; Savoia, Adele; Cristinziano, Adriano; et al. (Farmeconomia. Health Economics and Therapeutic Pathways, 2019)
AIM: To provide an updated picture of the therapies most commonly used in the advanced Non-Small Cell Lung Cancer (NSCLC) setting, together with the relevant costs.METHODS: This study considered the clinical records of patients affected by stage IIIb and IV NSCLC treated in the AORN dei Colli - Plesso Monaldi in Naples during the period January 2016-July 2017 and diagnosed since 2014, as well as the pathology lab database. Multivariate analyses were performed in order to identify the main predictors of time to next treatment and the main cost drivers.RESULTS: Data were collected on 575 patients, who were mainly affected by adenocarcinoma (62%) and squamous cell carcinoma (34%). 64% of patients were reported having been tested for molecular biomarkers (among the patients tested, 13% were EGFR+, 4% Alk t, and 1% ROS1 t). In accordance with the international guidelines, chemotherapy – as single agent or platinum-based doublets – was the prevalent first-line treatment, except among EGFR+ and ROS1 t patients, for whom the target therapy was authorized as first-line therapy. As second-line treatment, the target therapy and immune checkpoint inhibitors (nivolumab) were the most commonly used treatments. Drug expenditure per patient was remarkably higher in mutated patients (€ 29,053) versus wild-type patients, or patients with unknown mutational status (€ 11,854), who received just chemotherapy. The costs sustained in 2017 are proportionally higher than those sustained in 2016, mainlydue to the increasing eligibility to target therapy and immune checkpoint inhibitors and the wider biomarker analysis performed. From multivariate analyses, among the predictors of a longer time to next treatment (TTNT) were a better performance status and target therapy both in first and second line. The therapy for squamous cell carcinoma and other nonadeno histotypes turned out to be less expensive in patients treated just in the first line than that for adenocarcinoma and adenosquamous carcinoma. The use of immune checkpoint inhibitors in the second line results in increased costs compared to the use of chemotherapy. Also the target therapy in the first line results in an increase in the total costs with respect to chemotherapy in patients who received just a first-line therapy.CONCLUSIONS: Generally, in this study population, the treatments administered are in accordance with the international guidelines. The costs borne by the Health Systems are higher for the target therapy and the immune checkpoint inhibitors.